2017
DOI: 10.1021/acs.biochem.7b00388
|View full text |Cite
|
Sign up to set email alerts
|

A Dry Transition State More Compact Than the Native State Is Stabilized by Non-Native Interactions during the Unfolding of a Small Protein

Abstract: Defining the role of non-native interactions in directing the course of protein folding or unfolding reactions has been a difficult challenge. In particular, the extent to which such interactions play a productive role by stabilizing the structures of transition states (TSs) found on the folding and unfolding pathways of proteins is not known. On the contrary, it is thought that the TSs are expanded forms of the N state stabilized by native interactions, and it is not known whether non-native interactions can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…SH3 domains are small globular proteins and are considered to be archetypal of two-state folding proteins . They play important roles in signal transduction, where they provide the interaction surface for multimeric protein complexes. , The SH3 domain of the PI3 kinase was initially characterized as a cooperatively folding protein (two-state folder), , but subsequent equilibrium and kinetic folding studies showed that it (un)­folds via multiple intermediate states. Previous unfolding studies using HX-MS as a probe have shown that the unfolding of the PI3K SH3 domain is a highly heterogeneous process. , The initial structure opening events occur through a continuum of intermediate states. Only at a later stage does the remaining structure unfold in a cooperative manner.…”
mentioning
confidence: 99%
“…SH3 domains are small globular proteins and are considered to be archetypal of two-state folding proteins . They play important roles in signal transduction, where they provide the interaction surface for multimeric protein complexes. , The SH3 domain of the PI3 kinase was initially characterized as a cooperatively folding protein (two-state folder), , but subsequent equilibrium and kinetic folding studies showed that it (un)­folds via multiple intermediate states. Previous unfolding studies using HX-MS as a probe have shown that the unfolding of the PI3K SH3 domain is a highly heterogeneous process. , The initial structure opening events occur through a continuum of intermediate states. Only at a later stage does the remaining structure unfold in a cooperative manner.…”
mentioning
confidence: 99%
“…GdmCl was chosen as it typically unfolds proteins at lower concentrations when compared with urea denaturants and was previously used in kinetic experiments involving MT [ 33 , 42 ]. It has been shown that even in small proteins, transition states can be formed from non-native interactions in the presence of denaturants [ 43 ], but this was not observed for MT. It should be noted that the fragments did not unfold gradually, as indicated by the abrupt and dramatic change in the mass spectra.…”
Section: Discussionmentioning
confidence: 99%
“…More recent advances in mixer technology and detection methods [ 8 , 9 , 10 , 11 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] have resulted in major improvements in time resolution and sensitivity of continuous-flow instrumentation. By coupling continuous-flow mixing with a variety of detection methods, including tryptophan or tyrosine fluorescence, fluorescence resonance energy transfer (FRET), fluorescence life time, absorbance, circular dichroism, small-angle X-ray scattering and single-molecule spectroscopy, turbulent mixing devices have yielded a wealth of dynamic and structural information on early stages of protein folding on the microsecond-to-millisecond time scale [ 14 , 15 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%